2020
DOI: 10.1002/mco2.22
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Staphylococcus aureus infection regulates breast cancer cell metastasis via neutrophil extracellular traps (NETs) formation

Abstract: The formation of neutrophil extracellular traps (NETs) was recently identified as one of the most important processes for the maintenance of host tissue homeostasis in bacterial infection. Meanwhile, pneumonia infection has a poor effect on cancer patients receiving immunotherapy. Whether pneumonia-mediated NETs increase lung metastasis remains unclear. In this study, we identified a critical role for multidrug-resistant Staphylococcus aureus infection-induced NETs in the regulation of cancer cell metastasis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…This study suggested that expression of some key radiation signature genes appear to be altered by such infections. We also suggest that neutrophil extracellular traps (or NETs; Qi et al 2020) may activate biochemical pathways that are present in early radiation responses. An early step in the formation of these structures is chromosome decondensation followed by the fragmentation of DNA which act as extracellular fibers which bind pathogens (such as S. aureus) in a process similar to autophagy in neutrophils (NETosis).…”
Section: Discussionmentioning
confidence: 90%
“…This study suggested that expression of some key radiation signature genes appear to be altered by such infections. We also suggest that neutrophil extracellular traps (or NETs; Qi et al 2020) may activate biochemical pathways that are present in early radiation responses. An early step in the formation of these structures is chromosome decondensation followed by the fragmentation of DNA which act as extracellular fibers which bind pathogens (such as S. aureus) in a process similar to autophagy in neutrophils (NETosis).…”
Section: Discussionmentioning
confidence: 90%
“…The levels of plasma NETs in patients with lung cancer, cervical cancer, and pancreatic cancer are significantly higher than those in healthy controls and are related to tumor recurrence and metastasis. 194 In tumor metastasis, NETs are mainly involved in the spread of cancer cells and awakening dormant tumor cells. NETs can induce EMT of primary tumor cells in the early stage of metastasis and lead to the activation of inflammatory signaling pathways such as NF‐kB and STAT3, thereby enhancing the mobility and invasiveness of cancer cells and promoting metastatic growth.…”
Section: Components and Mechanisms Involved In Metastasismentioning
confidence: 99%
“…The potential use of the produced nanoparticles as antimicrobial materials against cancer-related, opportunistic bacterial strains was finally tested for a battery of five standard strains: E. coli [ 76 ], S. aureus [ 77 ], MRSA [ 78 ], P. aeruginosa [ 79 ] and E. faecalis [ 80 ]. These standard strains were selected due to their identified relationship, and locality, to some types of tumors, as well as their known response to the selected drugs [ 28 ].…”
Section: Resultsmentioning
confidence: 99%